The Isolation of Free-Living Nitrogen-Fixing Bacteria and the Assessment of Their Potential to Enhance Plant Growth in Combination with a Commercial Biostimulant - Elodie Buisset; Martin Soust; Paul T. Scott (Microbiology Research)
The development of microbial-based biostimulants to enhance the growth of crops and support a healthy and sustainable soil requires the isolation and large-scale industrial culture of effective microorganisms. In this study, work was undertaken to isolate and characterize free-living nitrogen-fixing bacteria capable of acting as biostimulants alone or by incorporation into and/or supplementation with a current commercial crop biostimulant for farmers. Free-living bacteria were isolated from soil, sugar cane mulch, and plant roots following preliminary culture in a nitrogen-free media that targeted specific groups of known diazotrophs. Following the identification of each isolate by 16S rDNA sequence analysis, isolates selected for further study were identified as most closely related to Priestia megaterium, Sphingobium yanoikuyae, and Burkholderia paludis. Each isolate was investigated for its capacity to promote plant growth in nitrogen-free media. Wheat seedlings were inoculated with the isolates separately, together as a consortium, or in combination with the commercial biostimulant, Great Land Plus®. Compared to no-treatment control plants, the fresh weights were higher in both the shoots (183.2 mg vs. 330.6 mg; p < 0.05) and roots (320.4 mg vs. 731.3 mg; p < 0.05) of wheat seedlings inoculated with P. megaterium. The fresh weights were also higher in the shoots (267.8 mg; p < 0.05) and roots (610.3 mg; p = 0.05) of wheat seedlings inoculated with S. yanoikuyae. In contrast, the fresh weight of the shoot and root systems of plants inoculated with B. paludis were significantly lower (p < 0.05) than that of the no-treatment control plants. Moreover, when Great Land Plus® was supplemented with a consortium of P. megaterium and S. yanoikuyae, or a consortium of P. megaterium, S. yanoikuyae, and B. paludis no promotion of plant growth was observed.